The Relationship Between Age With Oral Glucose Tolerance Test (OGTT) Level In The First-Generation Diabetes Mellitus (Dm) Type 2: Hubungan Usia dengan Nilai Tes Toleransi Glukosa Oral ( TTGO) Pada Generasi Pertama Penderita Diabetes Melitus (DM) Tipe 2 - I Made Adhi Setia W; Agustya Tjiptaningrum; Dian Isti angraini; Putu Ristyaning Ayu (Medula, 2021)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia that occurs as a result abnormalities in insulin secretion, abnormalities in insulin action or both. Risk factors for type 2 diabetes include age and genetic actors. The increase in the prevalence of DM in families with DM compared to the population in general is caused by genetic factors. An increase in the prevalence of DM in families with DM compared to the population in general raises the suspicion that genetic factors play an important role in the etiology of DM. Evidence of genetic heterogeneity as a cause of DM is the presence of various kinds of certain genetic syndromes due to mutations in various genetic loci. Early diagnosis of glucose disorders in blood is carried out by examining the oral glucose tolerance test (TTGO). The design of this study was an observational analytic study with a cross-sectional approach to 40 first-generation respondents with type 2 diabetes. The data were taken in the form of primary data, namely the results of blood tests of first-generation respondents with type 2 diabetes and TTGO value. The results showed that most of the first generation of type 2 diabetes mellitus sufferers aged 30-39 years experienced impaired glucose tolerance (70%) and normal TTGO values ​​were mostly at the age of 20-29 years (71.4%). There is a relationship between age and the TTGO value in the first generation of patients with type 2 diabetes who were studied